THE EFFECT OF CALCINATION TEMPERATURES ON THE PROPERTIES OF ZNO NANOPARTICLES SYNTHESIZED BY USING LEAVES EXTRACTS OF PINUS BRUTIA TREE - Ismail, Sherwan M.; Ahmed , Sabah M. (Science Journal of University of Zakho, 2023)
Pinus Brutia (PB) tree leaf extracts were used to produce zinc oxide (ZnO) nanoparticles. The study of the PB tree extracts at several calcination temperatures from (200 to 500) oC on the formation of ZnO NPs’ characteristics has been investigated using various characterization techniques. The chosen plant PB had its findings at both examinations of FTIR and UV-Visible spectroscopies shown and offered to be a superior option for the GS ZnO NPs at various pH levels. PB tree leaf extracts’ UV-visible spectra revealed one distinguishable absorption peak at 275.3 nm. The study of the FESEM results showed that the Green Synthesized (GS) ZnO NPs’ orientation, shape, and dimensions are significantly impacted by the calcination temperatures. The ZnO NPs are also shown by the XRD data to have hexagonal wurtzite crystal structures that have particle sizes at (002) peak falling within the range between (10 to 24) nm. The UV-Visible study of the ZnO NPs showed a strong peak absorbance for ZnO NPs that were calcined at various temperatures, with high UV absorption below 400 nm. The obtained energy band gap (Eg) is located in the region between (2.65 and 2.747) eV, narrowing as the calcination temperature rises. The ZnO NPs that were calcined at a temperature of 500 oC also had superior quality and outperformed those produced at other calcination temperatures, according to all of the analyzed results and properties of the ZnO NPs.